THE ROLE OF MENTAL ACCOUNTING IN PROMOTING BUSINESS ENTERPRISES: A STUDY OF SMALL AND MEDIUM SCALE BUSINESSES IN ENUGU STATE, NIGERIA - Onah, Georgina (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
Mental accounting reflects a series of cognitive operations that help organize financial activities and facilitate money management. However, empirical evidence linking mental accounting and small business growth are scarce. The present study aimed to investigate mental accounting as an accounting strategy that could enhance the development of small-scale enterprises in Nigeria. The study employed a cross-sectional survey design. Eighty-seven (n=87) small and medium-scale operators randomly selected from the Enugu state business hub participated in the survey.